Development of next generation Streptococcus pneumoniae vaccines conferring broad protection - Masomian, Malihe *; Zuleeza A,; Gew, Lai Ti *; Poh, Chit Laa * (MDPI, 2020)
Streptococcus pneumoniae is a major pathogen causing pneumonia with over 2 million deaths annually, especially in young children and the elderly. To date, at least 98 different pneumococcal capsular serotypes have been identified. Currently, the vaccines for prevention of S. pneumoniae infections are the 23-valent pneumococcal polysaccharide-based vaccine (PPV23) and the pneumococcal conjugate vaccines (PCV10 and PCV13). These vaccines only cover some pneumococcal serotypes and are unable to protect against non-vaccine serotypes and unencapsulated S. pneumoniae. This has led to a rapid increase in antibiotic-resistant non-vaccine serotypes. Hence, there is an urgent need to develop new, effective, and affordable pneumococcal vaccines, which could cover a wide range of serotypes. This review discusses the new approaches to develop effective vaccines with broad serotype coverage as well as recent development of promising pneumococcal vaccines in clinical trials. New vaccine candidates are the inactivated whole-cell vaccine strain (∆pep27∆comD mutant) constructed by mutations of specific genes and several protein-based S. pneumoniae vaccines using conserved pneumococcal antigens, such as lipoprotein and surface-exposed protein (PspA). Among the vaccines in Phase 3 clinical trials are the pneumococcal conjugate vaccines, PCV-15 (V114) and 20vPnC. The inactivated whole-cell and several protein-based vaccines are either in Phase 1 or 2 trials. Furthermore, the recent progress of nanoparticles that play important roles as delivery systems and adjuvants to improve the performance, as well as the immunogenicity of the nanovaccines, are reviewed.